2022-RA-629-ESGO Association of folate receptor α expression and tumor immune microenvironment in patients with cervical cancer. (20th October 2022) - Yazaki, Shu; Chiba, Yohei; Kojima, Yuki; Yoshida, Hiroshi; Takamizawa, Shigemasa; Kitadai, Rui; Saito, Ayumi; Okuma, Hitomi Suimyoshi; Nishikawa, Tadaaki; Shimoi, Tatsunori; Sudo, Kazuki; Noguchi, Emi; et al.
Abstract : Introduction/Background: Folate receptor α (FRα) is an attractive target for cancer treatment based on its expression profile. We previously reported that FRα expression was higher in cervical adenocarcinoma than in squamous cell carcinoma (SCC) and associated with poor survival (Takamizawa et al., AACR 2021). However, the relationship between FRα and the immune microenvironment remains unknown. Methodology: We performed immunohistochemical analysis of whole tumor sections from patients with cervical cancer who underwent primary surgery between 2000 and 2020 at our institution. FRα expression was evaluated using anti-FRα monoclonal antibody clone 26B3. FRα-positive and FRα-high were defined as ≥5% of tumor staining and as H-score ≥60. PD-L1 expression (clone 22C3) was assessed according to the combined positive score (CPS). The density of intratumoral CD3 and CD8 were calculated as the average number of positive cells in the five independent areas. The association between FRα expression and immune biomarkers was analyzed. Results: Overall, 123 patients were evaluated, and 67 were SCC and 56 were non-SCC. FRα-positive and FRα-high were identified in 72.4% and 27.6%. PD-L1 was positive (CPS≥1) in 75.6% and more commonly expressed in SCC (SCC vs. non-SCC; 83.5% vs. 66.1%, p=0.02). FRα expression showed a significantly negative correlation with PD-L1 expression (r=-0.22, p<0.001), and median (IQR) PD-L1 CPS was 20 (5–60) in FRα-negative and 5 (0–25) in FRα-positive group (p=0.04). FRα-positive was more frequent in PD-L1 CPS<10 groups than in PD-L1 CPS≥10 groups (81% vs. 64%, p=0.03). Median CD3 and CD8 counts were not different between FRα-negative and FRα-positive groups. Conclusion: In cervical cancer, FRα expression negatively correlates with PD-L1 expression and is more common in the PD-L1 CPS<10 groups. Our findings suggest that FRα-expression may be a potential therapeutic target for cervical cancer with low/negative PD-L1 expression.